Knowledge Management System for Railway Supply Chain Perspective - Mailasan Jayakrishnan; Abdul Karim Mohamad; Mokhtar Mohd Yusof (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2020)
Knowledge Management System (KMS) is a monitoring system that emphasizes the desired and actual performance of an industry. Aligning KMS to viably execute the Railway Industry methodology and supply chain operations utilizing legitimate knowledge management capabilities. Yet KMS controls the planning and priorities through action controls that emphasize on operational control level, result controls toward the strategic planning level, personnel controls on retaining the right operation with the right skills, and transaction control on the accurate and complete legal transactions for ensuring strategic management. Therefore, we have come up with a dynamic KMS for the Railway Supply Chain context that focuses on operational, tactical, and strategic perspectives on the information sources, value, analytics, and requirement for current and future drivers of an industry perspective. Moreover, this KMS aims to redesign the Information System by promoting a reductionist approach to problem-solving and best decision-making practices within an industry context.